Study of Operating and Marketing Strategy Factors in the Formulation of Strategies of Small Manufacturers - Abdollahi, Seyed Mohammad (Journal of Social and Development Sciences, 2011)
The main purpose of this research is to measure the relative importance of a selected number of primary operating and marketing factors which may be involved in the formulation of strategies of small manufacturers. One hundred manufacturing owner-managers in Iran were investigated. The marketing factors emphasized most often were improvement in product quality and reduction in product cost. However, improvements in customer service and in scheduling appeared to contribute more to actual firm performance. Overall, there seemed to be more emphasis on the production strategy factors than marketing factors as a means to gaining competitive advantage.